Economic and Statistical Review 1971 (Lagos: Federal Government Press, 1971)
Both government policies and programmes are directed at reducing the country's dependence on the petroleum sector, the sector remains the primary determinant of economic growth in Nigeria.
Index
lje 7/3/19
Arch
Keywords: Government policies; Statistical Review; Nigeria